The importance of site selection for radio astronomy - Roslan, Umar; Abidin, Z.Z.a; Ibrahim, Z.A (2014)
Radio sources are very weak since this object travel very far from outer space. Radio astronomy studies are limited due to radio frequency interference (RFI) that is made by man. If the harassment is not stopped, it will provide critic al problems in their radio astronomy scientists research. The purpose of this study is to provide RFI map Peninsular Malaysia with a minimum mapping techniques RFI interference. RFI mapping technique using GIS is proposed as a tool in mapping techniques . Decision-making process for the selection requires gathering information from a variety of parameters. These factors affecting the selection process are also taken account. In this study, various factors or parameters involved such as availability of telecommunications transmission (including radio and television), rainfall, water line and human activity. This study will benefit radio astronomy research especially in the RFI profile in Malaysia.